NSAIDs May Protect Against Age-Related Brain Atrophy - Bendlin, Barbara B.; Newman, Lisa M.; Ries, Michele L.; Puglielli, Luigi; Carlsson, Cynthia M.; Sager, Mark A.; Rowley, Howard A.; Gallagher, Catherine L.; Willette, Auriel A.; Alexander, Andrew L.; Asthana, Sanjay; Johnson, Sterling C. (Frontiers in Aging Neuroscience, 2010)
The use of non-steroidal anti-inflammatory drugs (NSAIDs) in humans is associated with brain differences including decreased number of activated microglia. In animals, NSAIDs are associated with reduced microglia, decreased amyloid burden, and neuronal preservation. Several studies suggest NSAIDs protect brain regions affected in the earliest stages of AD, including hippocampal and parahippocampal regions. In this cross-sectional study, we examined the protective effect of NSAID use on gray matter volume in a group of middle-aged and older NSAID users (n = 25) compared to non-user controls (n = 50). All participants underwent neuropsychological testing and T1-weighted magnetic resonance imaging. Non-user controls showed smaller volume in portions of the left hippocampus compared to NSAID users. Age-related loss of volume differed between groups, with controls showing greater medial temporal lobe volume loss with age compared to NSAID users. These results should be considered preliminary, but support previous reports that NSAIDs may modulate age-related loss of brain volume.